Characteristics of Governance for Domains beyond National Jurisdiction: Lessons for Future Outer Space Governance. Issue 2 (2nd September 2022) - Doucet, Gilles
ABSTRACT: Outer space is a domain beyond national jurisdiction where the governance regime is generally permissive. However, as actors and activities increase, additional governance is required. Other domains beyond national jurisdiction already benefit from functioning governance structures that have enabled activities to be conducted in an orderly, peaceful, and equitable manner. Although, as a physical domain, space is unique, the actors and interests are not. The actors are states and private entities. The interests are economic gain, safety and sustainability, national security, and international relations. Governance regimes for international civil aviation, telecommunications, and commercial shipping share common characteristics essential to achieving the consent and cooperation of states. Since the actors in the outer space domain are also states and private entities, and their interests are similar to those which they, by their very nature, pursue in other domains, the common characteristics shared among actors can guide the quest for future governance regimes of outer space.